Bottom-Up Control of the Groundwater Microbial Food-Web in an Alpine Aquifer - Karwautz, Clemens; Zhou, Yuxiang; Kerros, Marie-Emanuelle; Weinbauer, Markus G.; Griebler, Christian (Frontiers in Ecology and Evolution, 2022)
Groundwater ecosystems are typically poor in organic carbon and productivity sustaining a low standing stock of microbial biomass. In consequence, microbial food webs in oligotrophic groundwater are hypothesized to be bottom-up controlled. To date, quantitative information on groundwater microbial communities, food web interactions, and carbon flow is relatively lacking in comparison to that of surface waters. Studying a shallow, porous alpine aquifer we collected data on the numbers of prokaryotes, virus-like particles and heterotrophic nanoflagellates (HNFs), the concentration of dissolved (DOC) and assimilable organic carbon (AOC), bacterial carbon production (BCP), and physical-chemical conditions for a one year hydrological cycle. The potential effects of protozoan grazing and viral lysis onto the prokaryotic biomass was tested. Flow of organic carbon through the microbial food web was estimated based on data from the literature. The abundance of prokaryotes in groundwater was low with 6.1 ± 6.9 x 1e4 cells mL-1, seasonally influenced by the hydrological dynamics, with higher densities coinciding with a lower groundwater table. Overall, the variability in cell numbers was moderate, and so it was for HNFs (179 ± 103 HNFs mL-1) and virus-like particles (9.6 ± 5.7 x 1e5 VLPs mL-1). The virus to prokaryotes and prokaryote to HNF ratios ranged between 2 to 230 and 33 to 2,084, respectively. We found no evidence for a viral control of prokaryotic biomass, and the biomass of HNFs being bottom-up controlled. First estimations point at carbon use efficiencies of 0.2 to 4.2% with prokaryotic production, and carbon consumed and recycled by HNFs and phages to be of minor importance. This first groundwater microbial food web analysis strongly hints at a bottom-up control on productivity and standing stock in oligotrophic groundwater ecosystems. However, direct measurement of protozoan grazing and phage mediated lysis rates of prokaryotic cells are urgently needed to deepen our mechanistic understanding. The effect of microbial diversity on the population dynamics still needs to be addressed.